Anti-Angiogenesis Effects of Citrus and Flaxseed Extracts in a Chorioallantoic Membrane Assay - Capagas, Raymund; Callueng, Mary Jobhel; Diega, Daschel Alliyah; Gonzales, Aaliyah Dominique; Isleta, Benedict; San Agustin, Dhana (Journal of Interdisciplinary Perspectives, 2024)
Both Citrus aurantium (Dalandan) peels and Linum flavum (Golden Flaxseed) are rich sources of bioactive compounds with potential health benefits, including anti-cancer properties. This study assessed and compared the overall anti-angiogenesis activity of Citrus aurantium (Dalandan) peels and Linum flavum (Golden Flaxseed). Specifically, this study aimed to determine the minimum concentration of both Citrus aurantium (Dalandan) peels and Linum flavum (Golden Flaxseed) that exhibits anti-angiogenesis activity. It also aimed to determine the most potent concentration that is effective as an anti-angiogenesis agent. This study investigated the anti-angiogenic activity of Citrus aurantium (Dalandan) peels and Linum flavum (Golden Flaxseed) ethanolic extract using the fertilized duck embryo chorioallantoic membrane (CAM) assay, a widely accepted method for studying angiogenesis. Several concentrations of Citrus aurantium (Dalandan) peels and Linum flavum (Golden Flaxseed) ethanolic extracts were applied to the CAM of duck embryos, while control groups received saline and ascorbic acid. Preliminary findings suggest that Citrus aurantium (Dalandan) peels and Linum flavum (Golden Flaxseed) ethanolic extracts exhibit anti-angiogenesis activity. Further analysis, including quantifying blood vessel density and branching, provided insights into the comparative efficacy of the two extracts. Statistical analysis revealed that the most effective ethanolic concentration for Citrus aurantium (Dalandan) is 10%, while for Linum flavum (Golden Flaxseed) is 30%. The study concluded that Citrus aurantium (Dalandan) has the most effective anti-angiogenic activity compared to Linum flavum (Golden Flaxseed). This study contributes to understanding the potential use of Citrus aurantium (Dalandan) peels and Linum flavum (Golden Flaxseed) for therapeutic applications in cancer treatment through their anti-angiogenic properties. Moreover, this study underscores the importance of utilizing alternative models, such as the CAM assay, for rapid and cost-effective screening of anti-angiogenic agents.